KAJIAN LITERATUR: STUDI PEMETAAN SISTEMATIS INDIKATOR INOVASI SEKTOR PUBLIK - Lesmana Rian Andhika (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2020)
The public sector innovation indicator essentially simplifies and facilitates communication to achieve a goal. Public sector innovation can be assessed from productivity and dynamics performance, but public sector innovations at the most abstract level, associated with public sector authorities and legitimacy. Therefore, some academic studies are published to provide further knowledge of how public sector organizations act as learning and improvement tools. The purpose of this study is to further explore the results of previous studies relating to public sector innovation and various indicators using a systematic mapping study (SMS). Systematic Mapping Study (SMS) is used to construct research areas, compile, explain, and create catalogs of available evidence. This research article generates some information i.e., a first assessment of the public sector innovation indicator occurs due to the still bias of its indicators used due to the interpretation of the private sector concept. Second, a comparison of public sector innovations is used to view or act on diffusion innovations. Third, government intervention and policy in public sector innovation give the idea that innovation activities continue to be the main agenda of the government.